Review of Progress Annual Plan 1973-74 Andhra Pradesh - Planning Commission (Planning Commission, 1973)
The Planning Commission originally approved a Plan of Rs. 87.59 crores for 1973-74 comprising Central assistance of Rs. 55.21 crores and State’s resources of Rs. 32.38 crores and accordingly this outlay was included in the State Budget. Subsequently in October, 1973, the Government of India intimated a cut of 11.69 percent in the Central assistance for States for 1973-74, which amounted to Rs. 6.46 crores for Andhra Pradesh. Consequent on this reduction, the State Plan outlay for 1973-74 was reduced to Rs. 81.13 crores as indicated by the Planning Commission.
Finance and Planning (Planning Wing) Department, Government of Andhra Pradesh